Створення ВЧК: інтерпретація відомої проблеми - Подкур, Р. (З архівів ВУЧК-ГПУ-НКВД-КГБ, 2004)
The article is dedicated to the motivation of top party and state authority of Soviet Russia about the creation and formation of All-Russian Emergency Committee in the 1917–1918.